Paradigma Otonomi Estetika dalam Diskursus Barat dan Islam: Sebuah Analisis Kritis: The Paradigm of Aesthetic Autonomy in Western and Islamic Discourse: A Critical Analysis - Alifah Yasmin; Nala Alfia Chusna (Journal of Islamic and Occidental Studies, 2025)
The slogan “art for art’s sake” emerged in modern western aesthetics developed as a paradigm viewing the autonomy of art, free from ethical, religious, or practical purposes. According Théophile Gautier’s theory, this slogan emphasizes beauty as an end in itself. In the modern era, its influence is evident in artistic products that prioritize formal innovation, subjective expression, and aesthetic experience, such as abstract painting, experimental architecture, and conceptual art. Within the context of Islamic modern aesthetics, this paradigm interacts critically with traditional Islamic views that integrate beauty, ethics, and spirituality, producing both adaption and tension in contemporary Islamic art, design, and visual culture. This study employs a qualitative research method through philosophical analysis and critical textual interpretation of Kantian aesthtetics and modern Islamic discourse. The research indicates that “art for art’s sake” is characteristic of Western thinking, which is free from religious and spiritual values. Meanwhile, aesthetics in Islam involves the integration of ḥaqq, khayr, and jamāl. Beauty in Islam must contain goodness and truth, and be based on the values of tawhid and religion.